Cedrol ameliorates inflammatory bowel disease via mitochondrial biogenesis, gut microbiota restoration, and intestinal barrier repair - Xu, Mo-Rong; Lin, Chia-Hsin; Wang, Chung-Hsuan; Wang, Sheng-Yang (Frontiers in Pharmacology, 2026)
IntroductionInflammatory bowel disease (IBD) is a chronic inflammatory disorder of the gastrointestinal tract, primarily characterized by impaired intestinal barrier function. Enhancing mitochondrial ATP biosynthesis and restoring gut microbiota and metabolic balance may contribute to intestinal barrier repair and serve as a therapeutic strategy for IBD. Cedrol, the major component of Cunninghamia lanceolata var. konishii wood essential oil, is known for its anti-inflammatory and anti-bacterial properties. However, its effects on gut health remain unclear.MethodsTo evaluate the therapeutic effects of cedrol on inflammatory bowel disease (IBD), we assessed the expression of mitochondrial biogenesis and tight junction proteins using Western blotting. Additionally, we analyzed changes in gut microbiota and their metabolites, as well as colonic metabolites, through 16S rRNA gene sequencing, GC-MS, and 1H NMR analysis.ResultsThis study investigated the therapeutic potential of cedrol in an IBD model and found that it promotes colonic repair and enhances mitochondrial function by increasing ATP production and upregulating key proteins (SIRT-1, PGC-1α, Nrf2, p-AMPK/AMPK, TFAM). Furthermore, cedrol modulates gut microbiota balance by reducing Anaerostipes hadrus and Turicibacter sanguinis while increasing Blautia glucerasea and Anaerotaenia torta. It also elevates SCFA levels, supporting metabolic balance and the expression of tight junction protein expression, thereby strengthening the intestinal barrier and alleviating colitis.ConclusionIn conclusion, cedrol effectively restores mitochondrial function, modulates gut microbiota and metabolic balances, and enhances intestinal barrier integrity, highlighting its potential as a therapeutic candidate for IBD.